The Relationship Between Social Performance and Corporate Financial Performance - Hamidreza Salmani Mojaveri; Mohammadhadi Daftaribesheli; Amin Allahbakhsh (Universitas Pendidikan Indonesia, 2016)
This study investigates the relationship between social performance and corporate financial performance based on the information of companies listed in Tehran Stock Exchange - Iran. Today, economic entity has to identify the needs of their surrounding environment and community and in general interested parties to continue their survival and link with executive operation of the manufacturing of their products and by explaining the necessities of community provide the best services and achieve their organizational goals by selling more products. Overall, the process to identify community needs and interested parties and surrounding environment and provide services to them placed in social performance framework which is considered as the important issues to achieve success for organizations in today's competitive world. Therefore, we can say that the companies which do better their social functions financially might be in a desirable place than other competitor. In this study have been selected 90 companies of Tehran stock exchange based on elimination sampling and in order to investigate whether good social performance also leads to better financial performance. Financial variables are ROA and ROE and social variables contain five dimensions of Mark vinola model which obtain from tracking in financial statements and notes and based on score between -2 and +2. Finally, we conclude that there is no significant relationship between the social performance and corporate financial performance.